Sentence Recognition in the Presence of Competing Speech Messages Presented in Audiometric Booths with Reverberation Times of 0.4 and 0.6 Seconds - ABOUCHACRA, Kim S.; KOEHNKE, Janet; BESING, Joan; LETOWSKI, Tomasz (Archives of Acoustics, 2011)
This study examined whether differences in reverberation time (RT) betweentypical sound field test rooms used in audiology clinics have an effect on speechrecognition in multi-talker environments. Separate groups of participants listened totarget speech sentences presented simultaneously with 0-to-3 competing sentencesthrough four spatially-separated loudspeakers in two sound field test rooms havingRT = 0:6 sec (Site 1: N = 16) and RT = 0:4 sec (Site 2: N = 12). Speech recognitionscores (SRSs) for the Synchronized Sentence Set (S3) test and subjective estimatesof perceived task difficulty were recorded. Obtained results indicate that the changein room RT from 0.4 to 0.6 sec did not significantly influence SRSs in quiet or inthe presence of one competing sentence. However, this small change in RT affectedSRSs when 2 and 3 competing sentences were present, resulting in mean SRSs thatwere about 8–10% better in the room with RT = 0:4 sec. Perceived task difficultyratings increased as the complexity of the task increased, with average ratings similaracross test sites for each level of sentence competition. These results suggest thatsite-specific normative data must be collected for sound field rooms if clinicianswould like to use two or more directional speech maskers during routine sound fieldtesting.